2009
DOI: 10.1371/journal.pone.0007888
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Recent Positive Selection in Worldwide Human Populations: Evidence from Nearly 1 Million SNPs

Abstract: BackgroundGenome-wide scans of hundreds of thousands of single-nucleotide polymorphisms (SNPs) have resulted in the identification of new susceptibility variants to common diseases and are providing new insights into the genetic structure and relationships of human populations. Moreover, genome-wide data can be used to search for signals of recent positive selection, thereby providing new insights into the genetic adaptations that occurred as modern humans spread out of Africa and around the world.MethodologyW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
118
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 55 publications
15
118
0
1
Order By: Relevance
“…The population structure and phylogenic trees analyses performed here clearly showed the largest divergence between B. taurus (Hanwoo) and B. indicus (Asian zebu), which is consistent with previous studies and supports independent domestication of the two bovine species (Loftus et al, 1994;Gautier et al, 2010;Decker et al, 2014). Previous SNP-based studies in cattle, sheep and humans demonstrated that PC1 and PC2 primarily clustered breeds or populations according to their geographic origin (Herráez et al, 2009;Gauiter et al, 2010;Kijas et al, 2012). Similarly, our PCA analysis separated individual animals according to their geographic origin and domestication history.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The population structure and phylogenic trees analyses performed here clearly showed the largest divergence between B. taurus (Hanwoo) and B. indicus (Asian zebu), which is consistent with previous studies and supports independent domestication of the two bovine species (Loftus et al, 1994;Gautier et al, 2010;Decker et al, 2014). Previous SNP-based studies in cattle, sheep and humans demonstrated that PC1 and PC2 primarily clustered breeds or populations according to their geographic origin (Herráez et al, 2009;Gauiter et al, 2010;Kijas et al, 2012). Similarly, our PCA analysis separated individual animals according to their geographic origin and domestication history.…”
Section: Discussionsupporting
confidence: 91%
“…Ascertainment biases can be minimized by LD-pruning of closely associated SNPs and by analyzing haplotypes instead of individual SNPs (Herráez et al, 2009). We used different SNP data sets to assess the effects of ascertainment biases on population diversity indexes and differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using CEU/CHB/YRI populations as representative populations from the European, Asian, and African ancestral groups, the regions of natural selection associated with the gene list provided by Barreiro with overlap in one of two other publications are shown in Table 17 and Table 18 [84,95,96]. This table includes the number of loci in the bin, total binned variants from both populations, and the bin p-value.…”
Section: Regions Of Natural Selectionmentioning
confidence: 99%